2017
DOI: 10.1016/j.chemosphere.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the β-triketone herbicide tefuryltrione in drinking water sources and its degradation product in drinking waters

Abstract: Triketone herbicides are becoming popular because of their herbicidal activity against sulfonylurea-resistant weeds. Among these herbicides, tefuryltrione (TFT) is the first registered herbicide for rice farming, and recently its distribution has grown dramatically. In this study, we developed analytical methods for TFT and its degradation product 2-chloro-4-methylsulfonyl-3-[(tetrahydrofuran-2-yl-methoxy) methyl] benzoic acid (CMTBA). TFT was found frequently in surface waters in rice production areas at conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…That these TPs are very hydrophilic (log K ow < 0.1 at pH 7) most likely reduced Ratio of R PAC of TP to that of its parent pesticide in the present study. The recent increase of tefuryltrione use and its low acceptable daily intake suggest that tefuryltrione should be monitored in drinking water and source waters (Kamata et al 2017). Lin and Xing (2008) reported that the extent of adsorption of phenolic compounds to carbon nanotubes was in the order of phenol < catechol < pyrogallol, even though their log K ow were in the same order.…”
Section: Pac Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…That these TPs are very hydrophilic (log K ow < 0.1 at pH 7) most likely reduced Ratio of R PAC of TP to that of its parent pesticide in the present study. The recent increase of tefuryltrione use and its low acceptable daily intake suggest that tefuryltrione should be monitored in drinking water and source waters (Kamata et al 2017). Lin and Xing (2008) reported that the extent of adsorption of phenolic compounds to carbon nanotubes was in the order of phenol < catechol < pyrogallol, even though their log K ow were in the same order.…”
Section: Pac Adsorptionmentioning
confidence: 99%
“…The implication is that possible health effects related to the induction of gene mutation would be small, even though these compounds are found in tap water. In contrast, the MFP of tefuryltrione has not yet been reported, but chlorination completely transforms tefuryltrione into 2-chloro-4-(methylsulfonyl)-3-[(tetrahydrofuran-2-ylmethoxy)methyl]benzoic acid (CMTBA) (Kamata et al 2017), and CMTBA is reportedly very stable during chlorination (Kamata et al 2017). Because CMTBA does not induce mutagenicity (Food Safety Commission Government of Japan 2009), the MFP of tefuryltrione is expected to be negative.…”
Section: Mutagenicity Formation Potential Of Compounds Difficult To R...mentioning
confidence: 99%
“…Tefuryltrione decomposes to form 2-chloro-4-(methylsulfonyl)-3-[(tetrahydrofuran-2-ylmethoxy) methyl] benzoic acid (CMTBA) upon chlorine treatment, at a high conversion rate, and CMTBA was frequently detected in treated water and tap water. (Kamata et al, 2017). Fipronil yields its sulfone or additional forms in chlorine treatment (Teerlink et al, 2017).…”
Section: Detected Concentrations Of Pesticidesmentioning
confidence: 99%
“…Tefuryltrione, which has a low logK ow (2.62) and high water solubility [7], may impose potential risk to water resources. Recently, Kamata et al reported that tefuryltrione was found in river water with maximum concentration of 1.85 μg/L, and its degradation product, 2-chloro-4-methylsulfonyl-3-[(tetrahydrofuran-2-yl-methoxy)methyl]benzoic acid, existed extensively in drinking water [6]. Besides, diatoms were found to be most sensitive to herbicides that belong to the family of 4-hydroxyphenyl-pyruvate-dioxygenase inhibitors (including tefuryltrione), indicating its potential aquatic toxicity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tefuryltrione is now widely used for rice farming in Asian countries including China, Japan, and Korea . It has become quite popular and has begun replacing sulfonylurea herbicides, because of its brilliant herbicidal activity against sulfonylurea‐resistant weeds . However, the large quantity of tefuryltrione being used might not simply cause a high incidence of residual tefuryltrione in crops but might also lead to tefuryltrione dispersed or transferred to soil, and eventually into river systems by rainfall, leaching, or surface runoff, likely causing serial water pollution.…”
Section: Introductionmentioning
confidence: 99%